(untitled) (Research, Society and Development, 2021)
Objective: to analyze the meaning of music for patients in the postoperative period. Method: a qualitative study, in which 22 patients in the postoperative period participated in musical meetings. The musical meetings were held by a group of volunteers with music being applied to the chapel, performing in a vocal manner without instrumental accompaniment, alternating with the acoustic mode, using Ukulele®, Gianni® acoustic guitars, performing 12 meetings, lasting 40 minutes. After the intervention, the participants answered an interview and subsequently the data were analyzed using the thematic analysis and the aid of the IramuteQ® software. Results: with the analyzed data, it was possible to understand the perception of social actors in relation to music, with the following categories emerging: music and spirituality; the reception; the influence on emotional state and memories. Conclusion: it is concluded that music can be considered na instrument capable of evoking emotions and arousing feelings, favoring well-being and joy, producing and environment that refers to warmth and comfort, thus contributing to the humanization of nursing care.